Structural transformation and the urban growth shadows: County-level evidence from China, 1990–2020 - Enning Tang; Ming Gao; Wei You (Regional Science and Urban Economics, 2025)
This paper investigates whether a location's growth benefits or suffers from proximity to a big city and explores the underlying mechanisms. Using county-level data from China for 1990–2020, we find that an area's being close to a big city (in the 150–250 km range) reduces its decadal population growth rate by 2.9–3.6 percentage points relative to areas beyond 250 km, which we call the urban growth shadow effect. Initial agricultural employment share has the strongest power to explain whether the negative effect exists. The mechanism is consistent with lower opportunity costs of migration for people employed in agriculture, yet contrasts with core–periphery models that give transport costs a central role. Notably, this effect exhibits a temporal trend. Over time, being proximate to a big city becomes increasingly beneficial.